Two-Year Trajectories of Dental Anxiety in Parents and Their Association with Parents' and Children's Oral Healthcare Procedures in FinnBrain Birth Cohort Study - Satu Lahti; Eeva-Leena Kataja; Auli Suominen; Katri Palo; Mika Ogawa; Anu Kallio; Outi Räikkönen; Vesa Pohjola; Kari Rantavuori; Linnea Karlsson; Hasse Karlsson (MDPI AG, 2024)
We aimed to identify parents' dental anxiety trajectories and the association of the trajectories with the number of parents' and their children's oral healthcare procedures in the FinnBrain Birth Cohort Study. Dental anxiety was measured with the Modified Dental Anxiety Scale at gestational weeks (gw) 14 and 34, as well as 3 and 24 months (mo) after childbirth. Oral healthcare procedures from gw14 to 24 mo were obtained from the national patient data register and categorized as preventive and treatment. Trajectories were identified with latent growth mixture modelling for 2068 fathers and 3201 mothers. Associations between trajectories and procedures adjusted for education were analyzed using unordered multinomial logit models. Fathers' trajectories were stable low (80.1%), stable high (3.4%), stable moderate (11.0%), moderate increasing (3.9%) and high decreasing (1.6%). Mothers' trajectories were stable low (80.7%), stable high (11.2%), moderate increasing (5.3%) and high decreasing (2.8%). Mothers with decreasing dental anxiety had a higher number of preventive and treatment procedures. Fathers with decreasing dental anxiety had a higher number of preventive and treatment procedures, while fathers with increasing dental anxiety had fewer procedures. Children of mothers with stable low dental anxiety had higher number of preventive procedures. There seems to be a two-way association between dental anxiety trajectories and oral healthcare procedures.